Access to context-specific lexical-semantic information during discourse tasks differentiates speakers with latent aphasia, mild cognitive impairment, and cognitively healthy adults - Stark, Brielle C.; Dalton, Sarah Grace; Lanzi, Alyssa M. (Frontiers in Human Neuroscience, 2025)
PurposeMild language impairments experienced by adults with neurogenic communication disorders are often difficult to detect due to the lack of sensitive traditional performance-based measures. This is problematic since many adults who have mild language deficits experience daily activity and participation limitations that are undetected and not managed. This study evaluates the potential for variables derived through core lexicon analysis to differentiate two clinical groups (latent aphasia, MCI) from each other, and from a cognitively healthy adult group, across three different discourse tasks (Aim 1). Innovatively, it also contrasts the sensitivity with which each task differentiates the groups based on this metric (Aim 2).MethodsTranscribed connected speech data from TalkBank were analyzed for three discourse tasks (i.e., Sandwich Procedure, Cat Rescue Picture Description, and Cinderella Story) from three participant groups [Mild Cognitive Impairment (MCI) n = 30, stroke-induced latent aphasia n = 29, and Cognitive Healthy Adults (CHA) n = 56]. Aim 1 used one-way ANOVAs (or non-parametric equivalents) to identify differences in lexical variables (total number of core lexical items; proportion of core lexical items out of all words produced; and rate of core lexical items produced per second) between participant groups. Aim 2 used linear discriminant analysis with cross validation to characterize the sensitivity of discourse task in identifying lexical variables differentiating the participant groups.ResultsUnivariate analysis revealed significant differences among the three participant groups. During the Cinderella task, the latent aphasia and MCI groups produced significantly fewer core lexical items than CHAs, while their proportion of core lexical items to total tokens was higher than CHAs. The latent aphasia group produced core lexical items more slowly than the MCI group for all three discourse tasks. Finally, individuals with latent aphasia produced significantly fewer core lexical items during the Sandwich task than either the MCI or CHA groups. Aim 2’s sensitivity analysis revealed that number of core lexical items produced during the Cinderella task best differentiated the MCI group from CHAs, number of core lexical items produced during Sandwich best differentiated latent aphasia from CHAs, and core lexical items per second during Cinderella best differentiated latent aphasia from MCI.ConclusionOur study suggests that the Cinderella story is more sensitive than a picture description task for demonstrating the subtle lexical-semantic changes in MCI and latent aphasia compared to CHAs. Core lexicon appears to be a sensitive discourse metric to identify linguistic differences between CHAs and individuals with mild cognitive and/or language deficits. These findings further support calls to provide speech/language and cognitive therapy to individuals with MCI and/or latent aphasia.